Non-Fragile Sliding Mode Control of Uncertain Chaotic Systems - Leipo Liu; Zhengzhi Han; Zhumu Fu (Journal of Control Science and Engineering)
This paper is concerned with non-fragile sliding mode control of uncertain chaotic systems with external disturbance. Firstly, a new sliding surface is proposed, and sufficient conditions are derived to guarantee that sliding mode dynamics is asymptotically stable with a generalized H2 disturbance rejection level. Secondly, non-fragile sliding mode controller is established to make the state of system reach the sliding surface in a finite time. Finally, an example is given to illustrate the effectiveness of the proposed method.